Viruddhaahara in Ayurveda: Understanding the Impact of Incompatible Diets on Health and Lifestyle Diseases - P P, Hridya; Vasudev, Sarat (Journal of Neonatal Surgery, 2025)
The concept of incompatible food combinations holds a central place in Ayurvedic nutrition, emphasizing that improper food pairings can disrupt the body’s natural balance and lead to the accumulation of toxins (Ama). This traditional framework suggests that certain foods, when consumed together, can hinder digestion, create metabolic imbalances, and contribute to various health disorders. This paper explores the significance of Viruddha Ahara, its impact on digestion and metabolism, and the potential consequences for long-term health. Ayurvedic remedies for detoxifying the effects of such food combinations, including the use of herbs like Triphala, digestive boosters (Agnideepana), and metabolic enhancers (Pachana), are also discussed. Furthermore, the importance of mindful eating, balanced food combinations, and seasonal adjustments is highlighted as key factors for maintaining optimal health. The integration of Ayurvedic principles with modern dietary practices is proposed as a promising direction for enhancing personalized nutrition, promoting digestive health, and preventing chronic diseases. Future research should focus on scientifically validating Ayurvedic dietary interventions and exploring their role in personalized medicine, gut health, and chronic disease management. This approach has the potential to bridge ancient wisdom with modern nutritional science, offering a comprehensive path to better health.